Fatphobia in the news: a textual-discoursive analysis of discoursive representation and enunciative responsibility - Vasconcelos, Roberta Guimarães de Godoy e; Bernardino, Rosângela Alves dos Santos; Queiroz, Maria Eliete de (Revista Letras Raras, 2022)
This article aims to analyse how the discursive representation and the (non) assumption of enunciative responsibility are manifested in a piece of news about a fatphobia episode published in Claudia magazine in February, 2020, considering the management of points of view in the text by the first speaker-enunciator (S1/E1). For this, we assumea perspective which articulates the analysis plans of the text and the discourse, focusing in the semantic-pragmatic,enunciative and sociodiscursive, under the approach of the Textual Discoursive Analysis (ADAM, 2019, 2011, 2010)and the point of view theory (RABATEL, 2016a, 2016b). The paper was developed from a case study, following a qualitative approach and was based in the following categories: referencing and modification to the DRs; and the modalities and the indication of mediation charts to the ER; the socio-discoursive analysis and interdiscourse, to understand the ideological position of S1/E1 and the relation of voices reported in the text. In the analysis, we show that the management of voices by the S1/E1 is, on one hand, prototypical of the genre, when this discursive instancefocuses on other enunciators and assigns them the responsibility for the content of the POV; but, on the other hand,the lexical choices (referential and modifiers), the organization of linguistic signs (verbal and imagery) argumentatively guide the text, leading the interpretant to perceive the different DRs and the links of responsibility between S1/E1 andthe POVs of the victim of the fatphobia episode and with those who expressed their support and acceptance.